Network structure beyond food webs: mapping non‐trophic and trophic interactions on Chilean rocky shores. Issue 1 (1st January 2015) - Kéfi, Sonia; Berlow, Eric L.; Wieters, Evie A.; Joppa, Lucas N.; Wood, Spencer A.; Brose, Ulrich; Navarrete, Sergio A.
Abstract : How multiple types of non‐trophic interactions map onto trophic networks in real communities remains largely unknown. We present the first effort, to our knowledge, describing a comprehensive ecological network that includes all known trophic and diverse non‐trophic links among >100 coexisting species for the marine rocky intertidal community of the central Chilean coast. Our results suggest that non‐trophic interactions exhibit highly nonrandom structures both alone and with respect to food web structure. The occurrence of different types of interactions, relative to all possible links, was well predicted by trophic structure and simple traits of the source and target species. In this community, competition for space and positive interactions related to habitat/refuge provisioning by sessile and/or basal species were by far the most abundant non‐trophic interactions. If these patterns are corroborated in other ecosystems, they may suggest potentially important dynamic constraints on the combined architecture of trophic and non‐trophic interactions. The nonrandom patterning of non‐trophic interactions suggests a path forward for developing a more comprehensive ecological network theory to predict the functioning and resilience of ecological communities.